The Relationship Between Chronic Energy Deficiency and Anemia in Pregnant Women at The Madandan Community Health Center Rantetayo District Tana Toraja Regency - Kartini S (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
Chronic Energy Deficiency in pregnant women negatively impacts maternal health and fetal development, leading to weight loss, fatigue, weakness, and reduced immunity. CED also increases the risk of anemia, which can decrease oxygen supply and disrupt vital organ function. Anemia in pregnant women can cause fatigue, reduced productivity, and a higher risk of pregnancy and childbirth complications. This quantitative cross-sectional study aimed to analyze the relationship between CED and anemia in 40 pregnant women out of a total population of 64 at the Madandan Community Health Center, Tana Toraja. Data collection was carried out using a questionnaire, and the analysis employed a chi-square test. The results of Fisher's Exact Test indicated a significant association (p 0.000 < 0.05) between Chronic Energy Deficiency and anemia among pregnant women seeking treatment at the Madandan Community Health Center. The study recommends that community health centers enhance education on balanced nutrition for pregnant women through prenatal clinics, including up-to-date nutritional information, regular health monitoring, and provision of appropriate supplements to reduce the risk of anemia.